The HIV self-testing debate: where do we stand? - Marilou Gagnon; Martin French; Yamilee Hébert (BMC, 2018)
Abstract Background Emphasis on HIV testing as a gateway to prevention, treatment and care has grown tremendously over the past decade. In turn, this emphasis on testing has created a demand for new policies, programs, and technologies that can potentially increase access to and uptake of HIV testing. HIV self-testing (HST) technologies have gained important momentum following the approval of the over-the-counter self-tests in the United States, the UK, and France. While the renewed interest in HST has given rise to a number of high quality reviews of empirical studies conducted on this topic, we have yet to find an article that captures the extent of the debate on HST. Mapping the debate A critical review of the literature on HST was conducted and organized into three categories based on the focus of the article: 1) Empirical research, 2) Arguments, and 3) Context. We focused exclusively on the second category which included ethical analyses, policy analyses, editorials, opinion pieces, commentaries, letters to the editor and so forth. 10 lines of argument on HST were identified in the literature: 1) Individual - Public Health, 2) Strengths - Limits, 3) Benefits - Harms, 4) Screening - Testing, 5) Target - Market, 6) Health Care - Industry, 7) Regulation - Restriction, 8) Resource-Rich Settings - Resource-Limited Settings, 9) Ethical - Unethical, and 10) Exceptionalism - Normalization. Each line of argument is presented and discussed in the paper. Conclusion We conclude by providing examples of critical questions that should be raised in order to take the debate to another level and generate new ways of thinking about HST.